2009
DOI: 10.1111/j.1600-0714.2008.00720.x
|View full text |Cite
|
Sign up to set email alerts
|

Insight into the mechanisms underlying tumor response to boron neutron capture therapy in the hamster cheek pouch oral cancer model

Abstract: One of the mechanisms involved in BNCT-induced tumor control in our model would be an inhibitory effect on DNA synthesis. Apoptosis does not seem to have a significant role in BNCT-induced tumor control in our model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 39 publications
2
14
0
Order By: Relevance
“…Fujita et al stated that apoptosis was a form of cell death induced by BNCT [25]. While Aromando et al reported that apoptosis did not have a significant role in BNCT-induced hamster cheek pouch tumor control [26], and Kamida et al described that differences in apoptotic cells pre- and post-BNCT in human oral squamous cell carcinoma xenografts were minimal [27]. Whether BNCT can induce significant apoptosis rate in glioma cells in vivo and whether the pro-apoptotic effect is cell-type-dependant deserved further study.…”
Section: Discussionmentioning
confidence: 99%
“…Fujita et al stated that apoptosis was a form of cell death induced by BNCT [25]. While Aromando et al reported that apoptosis did not have a significant role in BNCT-induced hamster cheek pouch tumor control [26], and Kamida et al described that differences in apoptotic cells pre- and post-BNCT in human oral squamous cell carcinoma xenografts were minimal [27]. Whether BNCT can induce significant apoptosis rate in glioma cells in vivo and whether the pro-apoptotic effect is cell-type-dependant deserved further study.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the correlation between the cytotoxic effect of BNCT and the p53 status are limited [31,32], but more studies are employing high LET carbon-ion beams. Indeed, Iwadate et al[13] reported that high LET carbon-ion beams were more cytotoxic than low LET X-rays for glioma cells, and the effects of the carbon-ion beams were not dependent on the p53 gene status.…”
Section: Discussionmentioning
confidence: 99%
“…Aromando et al [32] reported that BNCT-induced control of hamster cheek pouch tumors would be an inhibitory effect on DNA synthesis and apoptosis does not have a significant role in tumor control. Masunaga et al [31] examined the effect of BNCT on SAS xenografts in nude mice.…”
Section: Discussionmentioning
confidence: 99%
“…Kreimann et al (2001) identified vacuolation as one of the morphological changes after BPAmediated BNCT in hamster buccal pouch tumours. Aromando et al (2009) indicated that BNCT had a marked inhibitory effect on DNA synthesis in hamster cheek pouch tumours and that apoptosis did not have a significant role in BNCT-induced tumour control. We found morphological changes such as chromosomal condensation, micronucleation, nuclear segmentation and vacuolation throughout the BNCT-treated SAS/neo and SAS/mp53 tumours.…”
Section: Discussionmentioning
confidence: 95%
“…Gamma ray irradiation, carbon-ion beams, iodine-131 and chemotherapeutic agents such as doxorubicin, cisplatin and paclitaxel have been shown to induce mitotic catastrophe (Ianzini et al 2006, Vakifahmetoglu et al 2008, Maalouf et al 2009). With regard to BNCT, apoptosis has been detected in a small proportion of treated SCC cells (Masunaga et al 2002, Kamida et al 2006, Aromando et al 2009), but other type of cell death such as mitotic catastrophe in response to BNCT has not. In the present study, we produced nude mouse tumours using oral SCC cells expressing wild-or mutant-type p53 with the same background and examined whether morphological alterations representing mitotic catastrophe can be induced by BNCT in a p53independent manner.…”
Section: Introductionmentioning
confidence: 98%